Mesenchymal stem cells as adjuvant therapy for limb lengthening in achondroplasia. Issue 3 (May 2019) - Memeo, Antonio; Verdoni, Fabio; Ingraffia, Caterina; Rossi, Laura; Pedretti, Leopoldo; D'Amato, Raffaele D.; Peretto, Laura; Mineo, Giuseppe V.
Abstract : Staged leg lengthening allows achondroplastic dwarfs to reach nearly normal height, but it takes long periods of external fixation and it can be burdened by delayed unions. Between 2009 and 2013, eight achondroplastic dwarfs showed delayed unions in the callus formation during femoral lengthening stages in our institute. We performed in-situ injections of bone marrow-derived stem cell concentrates. Patients underwent monthly clinical and radiographic assessment for determination of the healing rate. All eight patients showed an improvement in the regenerated bone, with an average healing index of 23.1 days/cm (range: 18.7–23.8 days/cm). The complete recovery of the delayed consolidation took on an average of 5.2 months (range: 2–10 months). The use of cellular therapy in these patients could represent an innovative application.